Laporan Studi Perancangan dengan BIM - Tomasowa, Riva (Bina Nusantara University, 2015)
Building Information Modeling (BIM) has grown in architectural education curriculum with many scholar researches escalated the report. However, the effectiveness of the deliverance has not been evaluated, especially from the student’s standpoint. This writing is the survey report that collected from Bina Nusantara University students, who accomplished 3 courses of architectural computing. The survey aims to give feedback of student understanding regarding the courses learning objectives. Surveys were conducted with open and closed questionnaires. Quantitatively the survey showed that they were self-convinced with the process they had taken through the semesters. The combination of learning strategies is the strength that should support the design studio with BIM.